SMART GAS CYLINDER - Kumar, Mohit; Gupta, Pragati; Wamiq, Mohd; Kumar, Abhishek (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
In this brief we are going to design smart gas cylinder which is capable of detection of leakage gas. The proposed design is basically inspired from the fire accidents due to the leakage of gas. This system is built using combination of microcontroller and GSM. The system has been design and implemented in a cost effective way so that commercialized user will take benefit from it.